Kinetic Modeling of the Electro-Fenton Process: Quantification of Reactive Oxygen Species Generation. (10th September 2015) - Qiu, Shan; He, Di; Ma, Jinxing; Liu, Tongxu; Waite, T. David
Graphical abstract: ABSTRACT: In this study, Electro-Fenton (E-Fenton) reactions at pH 3.0 were initiated by cathodic generation of H2 O2, with subsequent production of OH following the addition of Fe(II) or Fe(III) ions into the system. The variation in concentrations of H2 O2, Fe(II), total Fe and OH following addition of Fe ions into the E-Fenton system was investigated over a range of conditions. A kinetic model incorporating the key processes operating in the E-Fenton system was developed with particular attention given to (i) cathodic generation of H2 O2 and anodic formation of OH, (ii) production of OH via homogeneous Fenton reactions, and (ii) surface reactions including electro-sorption of Fe ions and cathodic reduction of Fe(III) to Fe(II) species resulting in the enhancement of production of OH via surface-located Fenton reactions.